Antifungal and antibacterial activities of four Malaysian sponge species (petrosiidae) - Qaralleh, Haitham; Syed Osman Idid, Syed Zahir Idid; Saad, Shahbudin; Darnis, Deny Susanti; Bakhtiar, M. Taher; Khaled M., Khleifat (Elsevier, 2010)
Aqueous and organic extracts from four marine sponges collected from the coastline of Malaysia were screened against six microorganisms, including the bacteria Staphylococcus aureus ATCC25923, Bacillus cereus ATCC11778, Pseudomonas aeruginosa ATCC27853, Escherichia coli ATCC35218, the yeasts Candida albicans ATCC10231 and Cryptococcus neoformans ATCC90112. All the sponge species in this study showed antibacterial activity against at least one bacterial strain and only one sponge species was significantly active against C. albicans. P. aeruginosa was considered resistant to all tested samples, since no inhibition zone was observed while the Gram-positive B. cereus was shown to be the most sensitive microorganism followed by C. albicans and S. aureus. The highest activity was obtained for the aqueous extract of Neopetrosia exigua against the Gram-positive bacteria B. cereus (inhibition zone 25 mm and MIC 0.07 mg/mL) and S. aureus (17.5 mm and 0.12 mg/mL) and against C. albicans (21 mm and 0.32 mg/mL). This extract is currently undergoing further analysis to identify the active compounds.